Tribological property evaluation, optimization and performance of waste sunflower oil based green cutting fluid with silicon dioxide nanoparticles as additive - Ajmal, N.; Maneesh, T.; Rani, S.; Mohanan, Visakh; Thampi, Ananthan D. (Recent Research in Science and Technology, 2023)
Mineral oil-based cutting fluids are hazardous and non-biodegradable, and their widespread usage has had a terrible effect on the environment and living things. The creation of a novel, ecologically sustainable cutting fluid technology is essential to avoid the above crisis. Commercial mineral oil alternatives are considered to possess identical lubricating properties as vegetable oils. Most vegetable oils are edible, so waste-cooking sunflower oil (WSO) is selected from this group to serve as the base stock for the green cutting fluid. The green cutting fluid is created using silicon dioxide nanoparticles as an additive and food-grade emulsifiers like Tween 80 and Span 80. According to the experimental findings, 0.05 weight percent silicon dioxide nanoparticles in the green cutting fluid performed better on a pin-on-disc tribometer.